Mycobacterium malmoense: an easily missed pathogen. - Hoffner, S E (1991)
The BACTEC system (Becton Dickinson, Sparks, Md.) was compared with culture on Löwenstein-Jensen egg medium for the detection of Mycobacterium malmoense in lymph node samples from children with lymphadenitis. It was found to be significantly more sensitive and rapid. The use of the BACTEC system is thus recommended as a complement to culture on solid media for the primary isolation of atypical mycobacteria, such as M. malmoense.